2020
DOI: 10.1530/jme-20-0176
|View full text |Cite
|
Sign up to set email alerts
|

Malic enzyme 1 (ME1) in the biology of cancer: it is not just intermediary metabolism

Abstract: Malic enzyme 1 (ME1) is a cytosolic protein that catalyzes the conversion of malate to pyruvate while concomitantly generating NADPH from NADP. Early studies identified ME1 as a mediator of intermediary metabolism primarily through its participatory roles in lipid and cholesterol biosynthesis. ME1 was one of the first identified insulin-regulated genes in liver and adipose and is a transcriptional target of thyroxine. Multiple studies have since documented that ME1 is pro-oncogenic in numerous epithelial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 79 publications
1
36
0
Order By: Relevance
“…On the other hand, it is reported that G6PD is not essential for K-Ras-driven tumors growth or metastasis [ 65 ], suggesting a less dependence on oxPPP of solid tumors in the context of glucose-deficient TME. Furthermore, the expression of IDH1 in prostate tumors and the expression of ME1 in gastric/colon/rectal/cancers were reported to be higher than adjacent non-tumor tissues [ 17 , 66 ]. Consequently, tumors possibly depend on IDH1 and ME1 more than adjacent non-tumor tissues, resulting in a therapeutic liability that can be exploited by targeting both IDH1 and ME1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is reported that G6PD is not essential for K-Ras-driven tumors growth or metastasis [ 65 ], suggesting a less dependence on oxPPP of solid tumors in the context of glucose-deficient TME. Furthermore, the expression of IDH1 in prostate tumors and the expression of ME1 in gastric/colon/rectal/cancers were reported to be higher than adjacent non-tumor tissues [ 17 , 66 ]. Consequently, tumors possibly depend on IDH1 and ME1 more than adjacent non-tumor tissues, resulting in a therapeutic liability that can be exploited by targeting both IDH1 and ME1.…”
Section: Discussionmentioning
confidence: 99%
“…ME1 is reported to regulate NADPH homeostasis to promote cancer growth and metastasis in gastric cancer [ 15 ] and nasopharyngeal carcinoma [ 16 ]. ME1 is found to be co-expressed with IDH1 and G6PD in diverse cancer cell lines [ 17 ], and ME1 can collaborate with mitochondrial IDH2 to maintain antioxidant systems to support tumor growth and metastasis [ 18 ]. Folate-dependent NADPH production by MTHFD and ALDH1L also contributes a large proportion to total NADPH pool in proliferating cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ME1 encodes malic enzyme 1 (ME1), which catalyzes the transformation of malate to pyruvate and promotes the formation of NADPH concomitantly. Prior studies reported that ME1 mediated the lipid metabolism through participating in lipid biosynthesis basically (Simmen et al, 2020). Numerous researches have provided the evidence of the pro-oncogenic role of ME1 in multiple tumors (Simmen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies reported that ME1 mediated the lipid metabolism through participating in lipid biosynthesis basically (Simmen et al, 2020). Numerous researches have provided the evidence of the pro-oncogenic role of ME1 in multiple tumors (Simmen et al, 2020). ALOX15B (Arachidonate 15-Lipoxygenase Type B) has been demonstrated as risk genes in colorectal cancer and lung squamous cell carcinoma (Yuan et al, 2020;Kim et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible therefore that the activation of the NRF2 pathway by radiation 129 contributes to increased lactate production by upregulating malic enzyme activity. The conversion of malate to pyruvate by malic enzymes generates NADPH, thus further contributing to antioxidant defenses, as well as to lipid and cholesterol biosynthesis 154 …”
Section: Changes To Major Metabolic Pathways Induced By Ionizing Radiationmentioning
confidence: 99%